Steindlian Models of Growth and Stagnation - Peter Skott; Peter Flaschel (University of Massachusetts, Department of Economics, 2004)
This paper examines Steindls original 1952 model and relates it to subsequent stagnationist models. The model is then extended by introducing endogenous changes in the markup and a reformulation of the investment function. These extensions address weaknesses of the simpler models, find support in Steindls writing and leave intact some of Steindls key results. In a further extension, we add a labour market and analyse the stabilizing influence of a Marxian reserve-army mechanism. The implications of this model for the effects of increased monopolization are largely in line with Steindls predictions.
Keywords: E24; E31; E32; 330; Steindl; accumulation; stagnation; markup; monopolization; reserve army of labour